El acompañamiento pastoral para jóvenes desde la comprensión psicológica y pedagógica humanista - Segarra Sánchez, Edgar Iván (2014)
The pastoral care for youth involves treating the theological, educational, psychological dimensions and teaching, the latter presents the associative array as the central experience of evangelizing youth ministry proposal for the integral growth of the young, who are accompanied by pastoralists with a basic profile to make, with vocation and professionalism, this task entrusted by the Church.